GARAP PERTUNJUKAN WAYANG KULIT JAWA TIMURAN - Nugroho, sugeng; Sunardi, S; Murtana, I Nyoman (Acintya, 2018)
This research is meant to prove the result of aesthetic aspect in wayang kulit performance of Jawa Timur style categorized as ‘kerakyatan (folk)’ pakeliran. The problem is analyzed based on the concept of ‘garap pakeliran’ offered by Sugeng Nugroho (2012) and the theory belongs to Umar Kayam (1981) concerning arts categorization. The method used is qualitative method with descriptive analysis. The data is collected through library study, documentation studies, interview, and field observation. The research finding shows that the current wayang kulit performance of Jawa Timur style cannot be categorized as folk art but rather to be kitsch. It represents a performing art that always change and move on along the time. It is attempted to be more interesting supposed to be survived and to earn money.Keywords: wayang kulit, Jawa Timuran, performance treatment.